Appraising perception, accessibility and uptake of DAT among patients with TB - C. Ogbudebe; B. Odume; I. Gordon; O. Chukwuogo; N. Nwokoye; S. Useni; E. Efo; M. Gidado; E. Aniwada; A. Ihesie; D. Nongo; R. Eneogu; et al. (Public Health Action, 2024)
INTRODUCTION: Poor adherence to TB treatment poses a significant public health threat to TB control programmes. The sustainability of directly observed treatment has been questioned because of its non-patient-centred approach and resource-intensive nature, and Digital Adherence Technologies (DATs) provide a suitable alternative. This study assessed the feasibility and acceptability of DATs among patients with TB. METHODS: This descriptive study was conducted in eight states in Nigeria among all patients with drug-susceptible TB. RESULT: A total of 230 patients (89.1%) own a phone that no one else uses, and 18 (7.0%) use a family phone. A higher proportion of 189 (73.3%) have airtime credit and 119 (46.1%) have internet credit on their phone. In addition, 216 (83.7%) stated that the reminders they received on their phone helped them remember to take their medicine. Only 11 (4.3%) patients missed a dose of the TB medicine. Equally, 11 (4.3%) patients had taken their TB medicine without using DAT. Of these, 7 (63.3%) did not use DATs because they forgot to text medication labels, and 3 (27.6%) did so because of poor network. Only four (1.6%) purchased additional items to support the use of DATs. CONCLUSION: DATs are acceptable in a wide variety of settings, even with reported challenges. Implementation efforts should ensure access, address technical challenges, and minimise additional cost to patients.